Remote control for operation and driving of ATLASCAR2 - Figueiredo, Diogo Augusto Rodrigues de (2021)
Obtaining a Self Driving Vehicle requires a well-planned collaboration between different areas and technologies, namely, it is crucial to effectively combine the sensory systems with the ability of remotely control the vehicle. This dissertation, integrated in the University of Aveiro Autonomous Driving project ATLASCAR2, links the vehicle’s actuators to the perception, navigation and decision making algorithms by creating a control and monitoring infrastructure and presents solutions to remotely control vehicle’s direction and speed. The control and monitoring infrastructure developed in this work uses the Controller Area Network of the vehicle for communication purposes and to access the current status of the vehicle by processing the messages exchanged between control units. In order to obtain solutions to remotely act on the direction and speed of the vehicle, the operation logic of the steering and propulsion systems of the Mitsubishi i-MiEV was studied and solutions that replicate the behaviour of the sensors used on these system are implemented. The results show the appropriateness of the developed solutions to control and monitor the vehicle and prove the feasibility of the method used to remotely control the steering wheel and accelerator pedal of the vehicle. However, for the braking system, an external mechanical actuator acting on the brake pedal is required to effectively control this system. Based on the results, the presented solutions show the great potential of utilizing the ATLASCAR2 to be used as a test platform of Autonomous Driving applications in a near future.